2008
DOI: 10.1007/s00417-007-0756-5
|View full text |Cite
|
Sign up to set email alerts
|

Lower corneal hysteresis in glaucoma patients with acquired pit of the optic nerve (APON)

Abstract: Corneal hysteresis in POAG patients with APON was significantly lower than in patients that did not have such structural changes of the optic disc. These findings may reflect pressure-independent mechanisms involved in the pathogenesis of such glaucomatous optic nerve changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 25 publications
4
62
0
1
Order By: Relevance
“…CH is lower in glaucoma damage, acquired optic nerve pitting, and progressive glaucoma. 2,15,[28][29][30][31] In glaucoma patients with low hysteresis, there is greater backward bowing of the lamina cribrosa in response to transient IOP elevation. 32 Furthermore, CH measurements may be useful in identifying patients with keratoconus and post-LASIK ectasia, as well as for monitoring biomechanical corneal properties before and after keratorefractive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…CH is lower in glaucoma damage, acquired optic nerve pitting, and progressive glaucoma. 2,15,[28][29][30][31] In glaucoma patients with low hysteresis, there is greater backward bowing of the lamina cribrosa in response to transient IOP elevation. 32 Furthermore, CH measurements may be useful in identifying patients with keratoconus and post-LASIK ectasia, as well as for monitoring biomechanical corneal properties before and after keratorefractive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This could suggest that corneal biomechanical properties may reflect viscoelastic properties of the lamina cribrosa, for example. 46 In keratoconus eyes, both CH and CRF seem to be lower than in a normal population (10.6±2.2 versus 8.7 ± 2.2 mmHg, and 10.0±2.5 versus 6.9±2.4 mmHg, respectively). 32 There is also a significant decrease of both CH and CRF following LASIK, 47 which could probably account for the changes observed in GAT measurements as described previously.…”
Section: Perkins Handheld Tonometer (Medtronic Solan Jacksonville Fmentioning
confidence: 80%
“…As some studies have reported differences in these parameters between glaucomatous and non-glaucomatous patients, 20,31,39,45,46,71,72 we believe that in the future these parameters might prove useful to better understand the pathophysiology in different eye conditions.…”
Section: Discussionmentioning
confidence: 93%
“…When other covariates were considered, this correlation lost its significance. Comparing CH values in POAG patients with and without acquired pits of the ONH, Bochmann et al 36 42 was not assessed in that study. On the other hand, Wells et al 13 correlated higher CH values (but not CCT) with greater changes in ONH topography after IOP increase.…”
Section: Discussionmentioning
confidence: 94%
“…6,[22][23][24][25][26] Previous studies have suggested that systemic and ocular factors, such as ageing, [27][28][29] chronically elevated IOP, [30][31][32] level of glaucomatous damage, 1,17,33 and disc size (scleral canal diameter), 34 could influence the susceptibility of an individual ONH to a given level of IOP. More recently, it has been suggested that other factors could be either directly or indirectly related to ONH response to pressure-induced damage, such as corneal parameters (both CCT and CH) 13,[35][36][37] and diabetes. 1,37,38 In glaucoma management, it is important to identify which factors are significantly related to an individual response to pressure-induced damage.…”
Section: Introductionmentioning
confidence: 99%